Real-world experience with anti–programmed cell death protein 1 immunotherapy in patients with esophageal cancer: A retrospective single-center study - Wang, Xinpeng; Cai, Lvjuan; Wu, Mengjing; Li, Guo; Zhu, Yunyun; Lin, Xinyue; Yan, Xue; Mo, Peng; Luo, Huachun; Fu, Zhichao (Frontiers in Oncology, 2022)
The "real world" data of PD-1 inhibitors in esophageal cancer (EPC) is still an unmet medical need, including the clinical efficacy and safety. 77 EPC data were studied retrospectively, the progression-free survival (PFS), risk factors (clinical stages larger than stage II, metastatic sites larger than 2, treatment lines larger than the first line, previous surgical treatment, CPS expression, etc) and the safety were analyzed. The median PFS for all patients was 7.2 months, Clinical stage > stage II, number of treatment lines ＞ first line was significantly correlated with prognosis (All P < 0.05). Subgroup analysis showed that the median PFS of patients with clinical stage ≤ II was better, the results were the same for the patients with ≤2 metastatic sites, first-line PD-1 inhibitors, and not previously received radical surgery(All P < 0.05). Meanwhile, The incidence of adverse reactions (AE) of varying degrees was 25.97% (20/77) in 20 patients, and 6.49% (5/77) of grade 3/4 AE. The highest AE was myelosuppression (15.58%), followed by liver function injury (7.79%). In addition, ≥2 lines of treatment and >2 metastatic sites predicted poor outcomes for patients with esophageal cancer who had failed first-line therapy or progressed with the combined immunotherapy and chemotherapy treatment strategy (All P < 0.05).